MOTIVASI PENGUNJUNG BERWISATA KE OBJEK WISATA HOT WATERBOOM SOLOK SELATAN - Dinata, Randy Surya (RC-INSTITUT, 2019)
This research originated from the observations of researchers on the motivation of visitors who did not travel optimally. This study aims to determine the motivation of visitors to travel to hot waterboom attractions. This research consists of 2 indicators of visitor motivation, namely: Internal (internal) and External (external). The type of this research is descriptive research with survey methods. The population of this study is visitors who traveled to hot waterboom. The sampling technique is non probability sampling, using incidental sampling. The number of samples in this study amounted to 30 people. Data collection techniques were conducted using a questionnaire (questionnaire) using a Likert scale that had been tested for validity and reliability. The next data was analyzed through descriptive analysis with the assessment categorization method based on the average score and percentage assessment. The results of the study concluded that in general the VISITORS 'MOTIVATION TOURISM TO THE HOT WATERBOOM TOURIST OBJECT SOLOK SOUTH 23.33% of respondents stated very well, 30% of respondents said good, 33.33% of respondents said enough, 3.33% of respondents said the category was not good and 0 % of respondents stated that they were not very good. While based on each indicator, namely: 1) internal indicators (in) as much as 66.66% of respondents stated very well, 13.33% of respondents said good, 10% of respondents said not good, 20% of respondents stated not good, and 3, 33% of respondents stated very bad, 2) external (external) indicators as much as 36.66% of respondents stated very well, 40% of respondents stated well, 10% of respondents stated less well, 6.66% of respondents stated not good, and 6, 66% of respondents said it was very bad.